Design privacy in contemporary ceramic art sculpture: نزار جواد الزبيدي (Al-Academy, 2016)
The importance of this research came through the question: Are there a privacy in the design in the ceramic arts, what are they? What are the basis of design for the ceramic art sculptures?The study refers to the design privacy in the contemporary ceramic arts, not as a serviceable art, but the art of being a dialectic collecting the arts across the craft and compositionThis research is the first study to look at the privacy of design and the connection with the formation of the large sizes ceramic art sculptures, and what they have as privacy of design and the way of formations.To highlight on the most prominent technical problems facing the ceramist in the production of so sculptural worksThe need for the study comes to help the workers in the field of art from this study and professionals in the technical and aesthetic educational institutions and students of primary and graduate studies in fine arts sections.The study came in four chapters: the first chapter, which contains the problem and the importance of research and the need for it and determine The most important terms contained in the search, and the second chapter, which contained, which included the following:1. Ceramic art and design.2. Privacy of ceramic material and design.3. Ceramic sculpture and design.The most important results that resulted from the study and analysis of samples are:1.Ceramic art sculpture is a new art structure invested modern design relations to Produce aesthetic values-based on creativity, It appeared in all the sample models, as well as it investment the structure of the laws of physics and the distribution of the blocks within a specific rule and a geometric build.2.The diversity in the glaze techniques confirmed the desire of the artist to create a visual art formative.3.The importance of instruments involved in the production of sculpture appeared as actively part in that process, as a clear example that the size of kilns for burning this ceramic arts sculptures sizes.4.Multi-color in ceramic sculpture Add high specificity singularity design in technical of ceramics arts in especially and in the fine art in general.